SETEL (Sehat dengan Telor):Generasi Bebas Stunting Program CRS STIKes Permata Nusanata dengan PT QL Agrofood: SETEL (Sehat dengan Telor):Generasi Bebas StuntingProgram CRS STIKes Permata Nusanata dengan PT QL Agrofood - Obar, Obar; Hartati, Sri; Balqis, Ummi Malika; Umaiyah, Siti; Waluya, Desi (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2023)
Abstract Program “SETEL: Generation Free from Stunting” aims to prevent stunting by providing eggs to children and pregnant women. The background reveals the complexity of stunting as a global health challenge that affects the physical and cognitive development of children. The purpose of this program is to provide adequate nutrition intake through eggs, which are rich in protein and essential nutrients, and to increase public awareness of the importance of giving eggs in preventing stunting. The method of implementing the program includes selecting targets, distributing eggs, nutrition education sessions, and monitoring child growth. The results of the program implementation show that giving eggs regularly has resulted in increased weight, height, and upper arm circumference in participating children. Nutrition education sessions successfully increased public understanding of the benefits of eggs in child nutrition. Collaboration with health institutions and communities helped successful implementation. The conclusion of this program is that giving eggs regularly can contribute to preventing stunting and improving the nutritional status of children. The success of this program encourages expansion in other areas facing similar problems. Suggestions are given to continue and develop the program, and to strengthen nutrition education as an important part in the effort to prevent stunting.